Dermoscopy of glomus tumour: a cross‐sectional study of 86 cases. (5th August 2022) - Álvarez‐Salafranca, M.; Bañuls, J.; Thomas, L.; Hirata, S.H.; Argenziano, G.; Medina, C.; Lacarrubba, F.; del Pozo, L.J.; Ara, M.; Zaballos, P.
Abstract: Background: Glomus tumours (GTs) are benign cutaneous neoplasms derived from the neuromyoarterial apparatus with a strong predilection for acral sites, especially the subungual space. Current data regarding dermoscopy of these lesions are very limited. Objectives: To analyse the dermoscopic structures and patterns seen in a large series of subungual (SUGTs) and extraungual glomus tumours (EUGTs) and to determine their diagnostic significance. Methods: Clinical and dermoscopic images of 86 histopathologically proven cases of GTs (47 SUGTs and 39 EUGTs) collected from 9 hospitals in Spain, France, Italy, and Brazil were evaluated for the presence of dermoscopic structures and patterns. Similarly, 189 and 185 dermoscopic images of other ungual tumours and other extraungual non‐pigmented tumours, respectively, were evaluated for the same structures and patterns. Finally, we evaluate diagnostic testing accuracy calculating sensitivity (S), specificity (Sp), and positive and negative predictive values of the different patterns for the diagnosis of GT. Results: Regarding SUGTs, four patterns were built from the combination of different structures. The pattern composed of a structureless purplish/red subungual spot with or without vessels reached the highest S (S1, 78.8%). The combination of a structureless purplish/red subungual spot and longitudinal erythronychia (LE) (S2) is highly specific (96.3%). Patterns S3 (proximal purplish/red subungual spot, LE, and distal notch) and S4 (bed subungual spot and onycholysis) are the most specific and exclusive of matrix and bed tumours, respectively. The most consistent pattern in EUGTs is composed of a structureless purplish‐white to reddish‐white homogeneous area and linear unfocused vessels (E) (S: 61.5%, Sp: 95.7%). EUGTs did not show lacunae, unlike other vascular tumours. Conclusions: Dermoscopy is helpful in improving the diagnostic accuracy of GTs, not only in SUGTs but also when these lesions arise out of the ungual apparatus.